2016
DOI: 10.1167/iovs.15-18303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Retinal Circulation Using Segmental-Scanning Doppler Optical Coherence Tomography in Anesthetized Cats

Abstract: Citation: Nagaoka T, Tani T, Song Y-S, et al. Evaluation of retinal circulation using segmental-scanning Doppler optical coherence tomography in anesthetized cats. Invest Ophthalmol Vis Sci. 2016;57:293657: -294157: . DOI:10.1167 PURPOSE. To study retinal blood flow (RBF) measurement reproducibility using segmentalscanning Doppler optical coherence tomography (DOCT) in vitro in glass capillaries and in vivo in anesthetized cats.METHODS. As a preliminary study, the flow rates of human blood through glass capil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 14 publications
0
39
0
Order By: Relevance
“…9 Our DOCT flowmeter is based on a commercially available spectral-domain OCT system (3D OCT-1 Maestro; Topcon Corp., Tokyo, Japan) operated at an 800-nm wavelength range. 16 Only the software was modified for blood flow imaging, where extra image-processing software and quantification software were newly developed to measure blood flow.…”
Section: Rbf Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Our DOCT flowmeter is based on a commercially available spectral-domain OCT system (3D OCT-1 Maestro; Topcon Corp., Tokyo, Japan) operated at an 800-nm wavelength range. 16 Only the software was modified for blood flow imaging, where extra image-processing software and quantification software were newly developed to measure blood flow.…”
Section: Rbf Measurementsmentioning
confidence: 99%
“…A detailed description has been published previously. 16 In the retina, most blood vessels run nearly parallel to the retinal surface except at the area around the optic nerve head. As h approaches 908, the measured velocity becomes very sensitive to the accuracy of h. To minimize this potential velocity measurement error, our Doppler blood flow measurements were performed where the Doppler angle h is considerably less than 908, that is,~808.…”
Section: Rbf Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recent studies [1][2][3][4] indicated that metrics that characterize the pulsatility of retinal BF are sensitive to early pathophysiological changes in the retina, therefore accurate assessment of retinal BF pulsatility can aid the early diagnosis of potentially blinding diseases. Previously, different optical imaging modalities, such as scanning laser ophthalmology, 5 laser Doppler velocimetry, 6 and retinal vessel analyzer 7 have been used for assessment of the pulsatility of retinal BF. In comparison, Doppler optical coherence tomography (DOCT) offers higher sensitivity and provides simultaneously both structural and BF/blood perfusion information about the imaged object, which offers an opportunity to examine the relationship between morphological and BF changes in the retina induced by retinal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method requires more complex and expensive design of the OCT system, while precise alignment of the two imaging beams at the same location in the retina can be difficult and time consuming. An alternative approach to measuring absolute retinal BF with DOCT is to utilize a dual-circle scanning pattern 6 and use the location displacement of blood vessels between the two circular OCT scans to calculate the Doppler angle. One limitation of this approach is that it is based on the assumption that the retinal blood vessel runs along a straight line between the two circular OCT scans, which is frequently not the case.…”
Section: Introductionmentioning
confidence: 99%